Photoconductive micro/nanoscale interfaces of a semiconducting polymer for wireless stimulation of neuron-like cells - Wu, Yingjie (2021)
We report multiscale structured fibers and patterned films based on a semiconducting polymer, poly(3-hexylthiophene) (P3HT), as photoconductive biointerfaces to promote neuronal stimulation upon light irradiation. The micro/nanoscale structures of P3HT used for neuronal interfacing and stimulation include nanofibers with an average diameter of 100 nm, microfibers with an average diameter of about 1 μm, and lithographically patterned stripes with width of 3, 25, and 50 μm, respectively. The photoconductive effect of P3HT upon light irradiation provides electrical stimulation for neuronal differentiation and directed growth. Our results demonstrate that neurons on P3HT nanofibers showed a significantly higher total number of branches, while neurons grown on P3HT microfibers had longer and thinner neurites. Such a combination strategy of topographical and photoconductive stimulation can be applied to further enhance neuronal differentiation and directed growth. These photoconductive polymeric micro/nanostructures demonstrated their great potential for neural engineering and development of novel neural regenerative devices.